Religion, Coloniality and Women’s Rights - SONIA DAYAN-HERZBRUN (Czech Journal of International Relations)
In response to Rola El-Husseini’s article, “Double Standards and Dissonance: Women’s Rights and Freedom of Religion in the Global North,” this paper addresses the French approach to secularism and women’s rights within a context of coloniality. Analyzing France’s secular framework, I explore the secular control over Muslim women’s attire and identity, tracing these regulations back to colonial practices. By examining how religious expression, particularly in relation to Islam, is selectively restricted, this commentary highlights the paradox of French “laïcité” as both a liberating and oppressive force, revealing ongoing colonial legacies in contemporary women’s rights discourse.